American Lotus, Yellow Lotus: Nelumbo lutea - Warner Orozco-Obando; Lyn Gettys (EDIS)
American lotus is an ideal native plant for constructed or restored wetland areas, where it provides shelter, habitat, and food for wildlife. It is an herbaceous aquatic perennial native plant that tolerates a wide range of conditions. The fragrant yellow flowers, huge round leaves, and persistent seed pods borne on stiff stalks high above the water make it both distinctive and visually striking. Native American tribes treated the American lotus as a sacred plant with mystical powers, and many tribes ate the large rhizomes and used parts of the plant for medicinal purposes. This 3-page fact sheet was written by Warner Orozco-Obando and Lyn Gettys, and published by the UF Department of Agronomy, March 2014.